MANAGEMENT OF INFORMATION STREAMS AT ALL HIERARCHY LEVELS OF TRAINING - Kirichek, G. G. (Radio Electronics, Computer Science, Control, 2010)
The training system is presented in the form of a multilevel construction of units interacting with other units and with the environment. The model of distributed system is developed for information streams control at all hierarchy levels of training and its further implementation in the information network.